Strategi Ekonomi Digital Grab dalam Meningkatkan Daya Saing Bisnis Transportasi Online - Reny Fitriana Kaban; Novita Fildzah; Syafira Risalah Amini (CV. Kalimasada Group, 2025)
This study aims to analyze the effectiveness of Grab's digital economy strategy in enhancing the competitiveness of online transportation businesses in Indonesia. Amid the rapid advancement of technology and increasing competition among digital platforms, Grab adopts an integrated digital ecosystem approach to offer comprehensive services such as ride-hailing, food delivery, digital payments, and financial services. This research uses a literature review method by examining various secondary data sources, including academic articles, industry reports, and recent statistical data. The findings indicate that Grab’s digital economy strategy has successfully strengthened its market position through technological innovation, service diversification, and the empowerment of driver-partners and MSMEs. Furthermore, Grab’s ability to adapt to regulations and market dynamics plays a crucial role in ensuring the sustainability of its business. However, challenges such as price competition, dependency on incentives, and demands for environmental sustainability remain pressing issues. This study contributes to the development of strategic management and digital economy knowledge and serves as a practical reference for players in the online transportation sector to formulate competitive and sustainable business strategies.